Legal Integrity in Contemporary Fiqh: An Analysis of Scholars’ Responses to Modern Fashion Issues in Indonesia - Harisah Harisah; Afidah Wahyuni; Sri Astutik Handayani; Kutsiyatur Rahmah; Muhammad Al Adib Habibul Haq (Fakultas Syariah UIN Sultan Aji Muhamamd Idris Samarinda, 2026)
The phenomenon of modern fashion development in Indonesia, particularly in the context of Muslim and Muslimah clothing, has brought about various changes in the social, cultural, and Islamic legal (fiqh) spheres, particularly regarding differing interpretations of the definition of the aurat, principles of modesty, and the use of religious symbols in the fashion industry for commercial purposes. This article examines how Islamic legal integrity is upheld by scholars in their responses to modern fashion trends through a contemporary fiqh approach. By examining fatwas and views from authoritative institutions such as the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah, this study highlights the debate surrounding the limits of aurat, the principle of modesty, and the commercialization of religious symbols in the fashion industry. It was found that most scholars strive to balance Sharia values with the cultural and economic expression needs of urban Muslim communities. However, challenges arise regarding the consistency of interpretation and social accountability for the issued fatwas, especially in light of the realities of social media, the creative industry, and global market dynamics. This study recommends the importance of dialogue between scholars, fashion industry players, academics, and the wider community as a strategic step to maintain legal integrity in the face of changing times. With a collaborative approach, Islamic law arguably remains relevant, is responsive, and capable of providing solid ethical guidance amid the rapid flow of modernity.